Cardamonin Lowers Intraocular Pressure and Inhibits Glaucoma Development in Steroid-Induced Rats by Activation of Nrf-2/Ho-1 Pathway - Fang, Yuan; Meng, Li; Zhang, Ruifen (Indian Journal of Pharmaceutical Education and Research, 2025)
Background Glaucoma, a progressive optic neuropathy characterized by optic nerve injury, is a pivotal cause of vision loss globally. Objective: The current work focuses on assessing the therapeutic role of cardamonin against experimentally-induced glaucoma in rats. Materials and Methods The experimental glaucoma in rats was induced by betamethasone, and then cardamonin was treated at 25 and 50 mg/kg concentrations. The Intraocular Pressure (IOP) level was assessed on a weekly basis. The glutamate and glutathione levels and the oxidative stress biomarker levels, including 8-Hydroxydeoxyguanosine (8-OH-dG), 4-Hydroxynonenal (4-HNE), and Malondialdehyde (MDA), were investigated using the commercial kits. The inflammatory markers and Nuclear factor erythroid 2-related factor (Nrf2) transcription factor/Hemoxygenase 1 (HO-1) levels were assessed using the commercial kits. Results The present findings of this study highlighted that cardamonin successfully reduced the IOP levels and consequently increased the RGCs level in the glaucoma-induced rats. The inflammatory cytokines and oxidative biomarkers (MDA, 8-OH-dG, and 4-HNE) levels were successfully reduced by the cardamonin treatment in the glaucoma-induced rats. Furthermore, the cardamonin effectively activated the Nrf-2/ HO-1 cascade in the glaucoma-induced rats, thereby mitigating the progression of glaucoma development. Conclusion The current findings showed that cardamonin treatment successfully reduced the development of steroid-induced glaucoma in rats. The findings of this work highlight that cardamonin could be a potentially effective option for the management of glaucoma.
Keywords: Glaucoma; Retinal Ganglial Cells; Nrf-2/HO-1 Pathway; Inflammation; 4-Hydroxynonenal.